TI_GERICHTE 17.2008.73 vom 21. Oktober 2009 , Diffamazione. Inammissibilità del ricorso per carenza di motivazione - TI Tribunale d'appello (2009)
Diffamazione. Inammissibilità del ricorso per carenza di motivazione